2021
DOI: 10.15259/pcacd.26.004
|View full text |Cite
|
Sign up to set email alerts
|

Sars-Cov-2 – The Latest Global Threat and the Prospect of Covid-19 Therapy With the Use of Chitosan

Abstract: Epidemics of infectious diseases have always been a threat to humanity and have contributed to increased mortality in the affected areas. This also applies to a new species of coronavirus identified in 2019, SARS-CoV-2, which is responsible for the COVID-19 pandemic. Despite preventive measures implemented all over the world to minimise the spread of the pathogen as well as the development of vaccines, which have been approved for emergency use, the situation is still worrying. Moreover, the problem is exacerb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Among the advantages of using natural resources, including chitosan, are the reduced side effects of the therapy and its high safety. In the last year, several publications have indicated the possibility of using biopolymers to prevent and to treat infections caused by the latest beta-coronavirus [ 95 ], and its effect can be linked to its diverse characteristics (Table 3 ).…”
Section: Treatments With Biomaterials Based On Chitosanmentioning
confidence: 99%
“…Among the advantages of using natural resources, including chitosan, are the reduced side effects of the therapy and its high safety. In the last year, several publications have indicated the possibility of using biopolymers to prevent and to treat infections caused by the latest beta-coronavirus [ 95 ], and its effect can be linked to its diverse characteristics (Table 3 ).…”
Section: Treatments With Biomaterials Based On Chitosanmentioning
confidence: 99%
“…Chitosan has been thoroughly researched for various potential uses including pharmaceutical, drug and gene delivery, dressings for wounds, treatment for cancer, burned skin, skin natural regeneration, functional coatings, beauty products, biological engineering, surgical tools, food industries, filtration of water for heavy metal adsorption, juice clarification and deacidification, food extended shelf life and preserving from microbial deterioration, food quality advancement, additives for food, and biodegradable packaging films formation (Kamari and Ghiaci 2016;Bajić et al 2019;Crini et al 2019;Cheba 2020;Tian and Liu 2020;Moradi et al 2021;Bashir et al 2022;Hoa et al 2022). Pieklarz and Modrzejewska (2021) suggested that chitosan-based treatments could be used to prevent and treat viral infections, including COVID-19, due to their antiviral properties. The US-Food and Drug Administration (US-FDA) has designated chitosan as a generally recognized as safe (GRAS) food additive (Zhang et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Chitosan (CH), due to its favorable biological properties [ 17 , 18 , 19 ] and ability to create various morphological structures, such as microgranules, sponges, membranes, films, hydrogels, and fibers [ 20 , 21 , 22 ], is widely studied for its applications in tissue engineering, ranging from the development of functional substitutes for human skin, through to solutions enabling the regeneration of bones, cartilage, and nerves [ 23 , 24 , 25 , 26 , 27 , 28 ]. The possibility of using chitosan as a carrier for pharmacological preparations and the treatment of hypercholesterolaemia is also interesting [ 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%